2022
DOI: 10.11591/ijphs.v11i4.21887
|View full text |Cite
|
Sign up to set email alerts
|

Does the increase in the cigarette excise tax affect cigarette consumption?

Abstract: <p>The level of cigarette excise rates is one of the factors of cigarette costs. However, it is unclear how high the cigarette excise rate should be in order to reduce smoking in Indonesia. The aim of this research was to see how effective the cigarette excise tariff policy was at lowering public cigarette usage. The study conducted a quantitative approach, employing survey data collection techniques on a number of smokers as well as in-depth interviews. The data indicated that a 12.5% increase in the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
0
0
3
Order By: Relevance
“…These studies found a significant negative relationship between excise tax increases and cigarette consumption. However, this result aligns with the findings of Susilawati et al (2022), which reported that 52% of respondents still choose to buy cigarettes of the same type despite price increases. This is because cigarette consumption is considered a necessity, and there is a preference for specific cigarette flavors, leading individuals to resist switching to other products despite price increases.…”
Section: Regression Resultssupporting
confidence: 89%
“…These studies found a significant negative relationship between excise tax increases and cigarette consumption. However, this result aligns with the findings of Susilawati et al (2022), which reported that 52% of respondents still choose to buy cigarettes of the same type despite price increases. This is because cigarette consumption is considered a necessity, and there is a preference for specific cigarette flavors, leading individuals to resist switching to other products despite price increases.…”
Section: Regression Resultssupporting
confidence: 89%
“…Cukai merupakan instrumen yang dapat digunakan pembuat kebijakan untuk mengurangi penggunaan produk tembakau, dan dapat secara khusus dimanfaatkan untuk mengurangi penggunaan produk yang berbahaya atau untuk mengurangi konsekuensi yang tidak diinginkan yang berbahaya bagi kesehatan masyarakat (Kowitt et al, 2022). Organisasi Kesehatan Dunia menyarankan agar pemerintah menaikkan cukai rokok hingga 70% untuk menaikkan harga rokok dan secara progresif mengurangi konsumsi rokok, Indonesia dapat meniru Thailand dan Filipina yang berhasil menjadikan kebijakan cukai rokok sebagai regulator utama yang mempengaruhi prevalensi rokok (Susilawati et al, 2022).…”
Section: Pembahasan Implementasi Cukai Rokok Elektrik DI Indonesiaunclassified
“…Indonesia dari tahun ke tahun sudah menaikkan tarif cukai rokok secara konsisten selama beberapa tahun terakhir, tetapi indeks keterjangkauan atas rokok tidak berubah secara signifikan. Hal tersebut menjadikan kegunaan cukai rokok dipertanyakan, karena tidak mempengaruhi perilaku masyarakat untuk berhenti merokok (Susilawati et al, 2022). Berdasarkan fenomena tersebut dikuatkan oleh data dari Global Tobacco Epidemic Report 2019 WHO dalam Susilawati (2022) yang menunjukkan bahwa Indonesia merupakan salah satu negara kawasan Asia Pasifik dengan harga rokok terendah pada tahun 2018.…”
Section: Pembahasan Implementasi Cukai Rokok Elektrik DI Indonesiaunclassified
See 1 more Smart Citation